Dosimetric impact of variable bladder filling on IMRT planning for locally advanced carcinoma cervix - Soumya Dutta (Journal of the Egyptian National Cancer Institute, 2020)
Abstract Background To evaluate the dosimetric impact of variable bladder filling on target and organ at risk (OARs) in cervical cancer patients undergoing chemoradiation. Forty consecutive patients with cervical cancer underwent radiotherapy planning as per the departmental protocol. All patients were asked to empty their bowel and bladder before simulation and catheterization was done. Normal saline was instilled into the bladder through Foleys till the patient had a maximal urge to urinate. Pelvic cast fabrication and CT simulation was done. Then, 30%, 50%, and 100% of the instilled saline was removed and rescans taken. Planning was done on full bladder (X) and the same plan applied to the contours with bladder volumes 0.7X (PLAN70), 0.5X (PLAN50), and empty (PLAN0). A dose of 50 Gy/25# was prescribed to the PTV and plans evaluated. Intensity-modulated radiotherapy plans with full bladder were implemented for each patient. Shifts in the center of mass (COM) of the cervix/uterus with variable bladder filling identified were noted. Statistical analysis was performed using SPSS software. A p value < 0.05 was considered significant. Results Bladder volume in 70%, 50%, and empty bladder planning was 78.34% (388.35 + 117.44 ml), 64.44% (320.60 + 106.20 ml), and 13.63% (62.60 + 23.12 ml), respectively. The mean dose received by 95% PTV was 49.76 Gy + 1.30 Gy. Though the difference in target coverage was significant between PLAN100 and other plans, the mean difference was minimal. A decrease in bladder filling resulted in an increase in OAR dose. Variation in the increase in dose to OARs was not significant if bladder filling was > 78.34% and > 64.44% of a full bladder with respect to the bowel and rectal/bladder doses, respectively. Inconsistent bladder filling led to a maximal shift in COM (uterus/cervix) in the Y- and Z-axis. Conclusion Bladder filling variations have an impact on cervico-uterine motion/shape, thereby impacting the dose to the target and OARs. It is recommended to have a threshold bladder volume of at least 70–75% of optimally filled bladder during daily treatment. Trial registration Institutional review board (IRB) registered by Drug Controller General (India) with registration number ECR/10/Ins/DC/2013. Trial Registration number - RGCIRC/IRB/44/2016, registered and approved on the 14th of May 2016.